2017
DOI: 10.1016/j.ijhydene.2016.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Development of a polymer electrolyte fuel cell dead-ended anode purge strategy for use with a nitrogen-containing hydrogen gas supply

Abstract: Graphical Highlight2 Highlights (<85 characters per highlight; 3-5 highlights needed)  Nitrogen-containing hydrogen gas mix supplied to PEFC dead-ended anode. Voltage decay seen as both nitrogen content in fuel and fuel cell load increase. Design of Experiments methodology used to assess stack efficiency. Optimised purge strategy identified for nitrogen-containing hydrogen fuel. AbstractThe effect of nitrogen content within the hydrogen fuel supplied to a polymer electrolyte fuel cell (PEFC) operating in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, no CO 2 or CO emissions are created during the decomposition of ammonia to produce hydrogen. The gas produced by this reaction is attractive as a fuel for fuel cells that operate at low temperatures, such as polymer electrolyte fuel cells (PEFCs) because the Pt electrode is easily poisoned by CO. 6,7 Numerous metals, including Ru, 8 Ir, 9 Ni, 10 Rh, 11 Pt, 12 Pd, 13 Co, 14 and Fe, 15 have been demonstrated to act as catalysts for the breakdown of ammonia in earlier studies. Ru is well known for being the most effective catalyst in the group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no CO 2 or CO emissions are created during the decomposition of ammonia to produce hydrogen. The gas produced by this reaction is attractive as a fuel for fuel cells that operate at low temperatures, such as polymer electrolyte fuel cells (PEFCs) because the Pt electrode is easily poisoned by CO. 6,7 Numerous metals, including Ru, 8 Ir, 9 Ni, 10 Rh, 11 Pt, 12 Pd, 13 Co, 14 and Fe, 15 have been demonstrated to act as catalysts for the breakdown of ammonia in earlier studies. Ru is well known for being the most effective catalyst in the group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no CO 2 or CO emissions are created during the decomposition of ammonia to produce hydrogen. The gas produced by this reaction is attractive as a fuel for fuel cells that operate at low temperatures, such as polymer electrolyte fuel cells (PEFCs) because the Pt electrode is easily poisoned by CO. , …”
Section: Introductionmentioning
confidence: 99%
“…As water and nitrogen accumulate and are removed from the anode, hydrogen can reach the active catalyst area and provide sufficient fuel for the electrochemical reaction of the battery, thereby restoring battery performance and minimizing the battery degradation caused by insufficient fuel [20]. Overall, the purging strategies can be classified into the three following categories: (1) fixed purge intervals with different current density [21,22]; (2) slopes of the voltage decrease [14]; and (3) fuel utilization and voltage drop [23]. Sasmito et al [21] adopted a fractional factorial approach to examine the effects of cathode air-stoichiometry, the anode purging period, and the purging duration on the performance of a DEA-PEMFC.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Siegel et al 27 pointed out that accumulation of nitrogen would cause voltage attenuation. Okedi et al 28 conducted experiments with 75% hydrogen and 25% nitrogen, and found that the voltage loss was related to the accumulation of nitrogen, and was more significant under high current density. Uniformity is one of the most important indicators for evaluating the performance of a fuel cell stack, and the "Buckets effect" makes the stack depend on the lowest single-cell voltage 29,30 which can even lead to reverse polarity when the single-cell voltage is too low.…”
Section: Introductionmentioning
confidence: 99%